A flora of northeastern Minnesota - Lakela, Olga (University of Minnesota Press, 1965)
A Flora of Northeastern Minnesota was first published in 1965. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. A manual for the identification of the ferns, fern allies, flowering plants, trees, shrubs, and herbs of Minnesota's Arrowhead region, this volume lists 113 botanic families and describes 1,300 species, with keys for identification. There are 80 line drawings of plant species and 419 maps showing distribution.